Who is bowling alone? Quantile treatment effects of unemployment on social participation - Lars Kunze; Nicolai Suppa (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
This article examines heterogeneity in the effect of unemployment on social participation. Whereas existing studies on this relationship essentially estimate mean effects, we use quantile regression methods to provide a broader and more complete picture. To account for the potential endogeneity of job loss, we estimate quantile treatment effects (on the treated) based on entropy balancing and focus on unemployment due to plant closures. Using German panel data, we show that the effect of unemployment varies across the distribution of public social activities. It is large and negative for individuals in the middle and lower part of the distribution of public activities, whereas those participating a lot are not affected. By contrast, the effect of unemployment on private social participation is virtually zero for individuals at the lower part of the outcome distribution and weakly positive in the middle. Our findings suggest that active labor market policies should account for target-group specific elements, tailored to those individuals which are most adversely affected by unemployment.
Keywords: J65; C21; I31; 330; unemployment; social participation; plant closure; quantile treatment effects; entropy balancing